THU0673 The european consensus finding study group (ECFSG) helps characterizing new tentative reference standards for autoantibody measurement. (15th June 2017) - Rönnelid, J; Dahle, C; Blüthner, M; Feist, E; Dolman, C; Thorpe, SJ; Monogioudi, E; Zegers, I; Meroni, PL; Hamann, D; ,
Abstract : Background: Since 1988, the European Consensus Finding Study Group on autoantibodies in rheumatic diseases (ECFSG), also known as the EULAR autoantibody study group, has been distributing sera with unspecified antibodies to European laboratories (presently n=43) for evaluation of different autoantibody measurement techniques in a clinical context. Use of reference materials helps to align test results by adopting internationally used measurement units, but reference materials are missing for many autoantibody specificities. Objectives: Recently the scope for ECFSG was expanded to also include unbiased autoantibody characterization of serum/plasma specimens planned to constitute raw material for production of future autoantibody reference materials. Methods: Four samples were included to be evaluated as future tentative international reference materials for four different autoantibody specificities: double stranded/native DNA (dsDNA, evaluated in 2013/14), IgG anti-b2GP1, proteinase 3 (PR3) and myeloperoxidase (MPO, evaluated in 2015/16). The samples were included "blind", and evaluated broadly for multiple autoantibody specificities by participating laboratories. Results: All or almost all participating laboratories detected the target specificities, and all four samples showed restricted autoantibody specificities related to the target specificity. Anti-dsDNA was detected by all laboratories using Crithidia luciliae, ELISA/EIA, FARR assay or ALBIA and all labs reported a homogenous ANA pattern. Other specificities were restricted to histones, nucleosomes and anti-Ku. All laboratories but one detected IgG anti-b2GP1 and IgG anti-cardiolipin, mostly in high levels, in the tentative IgG anti-b2GP1 reference standard, whereas corresponding IgA and IgM antibodies were absent. All laboratories detected anti-MPO, mostly monospecific and in high levels together with P-ANCA pattern in the anti-MPO reagent. Anti-PR3 and C-ANCA pattern, mostly in high levels/titers were detected by all laboratories in the tentative anti-PR3 reagent, irrespective of method used. Conclusions: The expanded scope of ECFSG has enabled broad characterization of new tentative autoantibody reference standards. The anti-dsDNA specimen has been processed by the National Institute for Biological Standards and Control (NIBSC) for consideration as the 2nd WHO anti-dsDNA reference standard. The other materials are basis for certified reference material for IgG anti-myeloperoxidase (ERM-DA476/IFCC), and the candidate reference materials for IgG anti-proteinase 3 (in certification) and for IgG anti-b2PG1 (in evaluation) from the Joint Research Centre. Disclosure of Interest: None declared